CAPTCHA as a Visual Performance Metric in Active Macular Disease - Gautam Vangipuram; Aaron Y. Lee; Kasra A. Rezaei; Lisa C. Olmos De Koo; Yewlin E. Chee; Jennifer R. Chao; Catherine Egan; Cecilia S. Lee (Journal of Ophthalmology)
Purpose. CAPTCHA (completely automated public turing test to tell computers and humans apart) was designed as a spam prevention test. In patients with visual impairment, completion of this task has been assumed to be difficult; but to date, no study has proven this to be true. As visual function is not well measured by Snellen visual acuity (VA) alone, we theorized that CAPTCHA performance may provide additional information on macular disease-related visual dysfunction. Methods. This was designed as a pilot study. Active disease was defined as the presence of either intraretinal fluid (IRF) or subretinal fluid (SRF) on spectral-domain optical coherence tomography. CAPTCHA performance was tested using 10 prompts. In addition, near and distance VA, contrast sensitivity, and reading speed were measured. Visual acuity matched pseudophakic patients were used as controls. Primary outcome measures were average edit distance and percent of correct responses. Results. 70 patients were recruited: 33 with active macular disease and 37 control subjects. Contrast sensitivity was found to be significantly different in both the IRF (p<0.01) and SRF groups (p<0.01). No significant difference was found comparing the odds ratio of average edit distance of active disease (IRF, SRF) vs. control (OR 1.09 (0.62, 1.90), 1.10 (0.58, 2.05), p=0.77, 0.77) or percent correct responses of active disease vs. control (OR 0.98 (0.96, 1.01), 1.09 (0.58, 2.05), p=0.22,0.51) in CAPTCHA testing. The goodness of fit using logistic regression analysis for the dependent variables of either IRF or SRF did not improve accounting for average edit distance (p=0.49, p=0.27) or percent correct (p=0.89, p=0.61). Conclusions. Distance VA and contrast sensitivity are positively correlated with the presence of IRF and SRF in active macular disease. CAPTCHA performance did not appear to be a significant predictor of either IRF or SRF in our pilot study.